2022
DOI: 10.1111/gcb.16392
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of altered precipitation regimes on soil nitrogen cycling at the global scale

Abstract: Changes in precipitation regimes can strongly affect soil nitrogen (N) cycling in terrestrial ecosystems. However, whether altered precipitation regimes may differentially affect soil N cycling between arid and humid biomes at the global scale is unclear. We conducted a meta‐analysis using 1036 pairwise observations collected from 194 publications to assess the effects of increased and decreased precipitation on the input (N return from plants), storage (various forms of N in soil), and output (gaseous N emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 112 publications
3
15
1
Order By: Relevance
“…Leaf N content and C:N and N:P ratios were sensitive to medium DPPT (Figure 4b,d,f), providing additional evidence that DPPT primarily influenced the N cycle in plants. In humid areas, leaf N content, and C:N and N:P ratios exhibited high sensitivity to DPPT (Table S1), aligning with previous studies that drought increased plant N uptake in humid areas (Wu et al, 2022). One possible mechanism is that drought reduced N losses through leaching, particularly in humid areas (Austin & Vitousek, 2000; Hao et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Leaf N content and C:N and N:P ratios were sensitive to medium DPPT (Figure 4b,d,f), providing additional evidence that DPPT primarily influenced the N cycle in plants. In humid areas, leaf N content, and C:N and N:P ratios exhibited high sensitivity to DPPT (Table S1), aligning with previous studies that drought increased plant N uptake in humid areas (Wu et al, 2022). One possible mechanism is that drought reduced N losses through leaching, particularly in humid areas (Austin & Vitousek, 2000; Hao et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The NH 4 + -N concentration was higher under 100% soil water content across all freeze-thaw treatments. This result is contrary to the results reported by Wu et al [60], who found that precipitation decreased the soil NH 4 + -N. However, the increase in the NH 4 + -N concentration under 100% soil water content did not happen under CK, but was observed under the LF, SFQT, and QFST treatments, wherein the mean concentration increased approximately twofold as compared to under 30% and 60% soil water content levels. We supposed that a high water content enhances the positive effect of freezing on the NH 4 + -N concentration.…”
Section: The Changes In Soil Nutrients Enzyme Activities and Soil Mic...contrasting
confidence: 97%
“…In our study, warming reduced soil inorganic N concentrations, which was consistent with some previous studies (Durán et al, 2016; Zhang et al, 2005). This might be due to reduced organic matter decomposition, limited ion mobility in drier soils (Jarvi & Burton, 2018; Joseph et al, 2021), and/or increased N leaching loss under warming (Wu et al, 2022). However, soil N availability is relatively higher in subtropical areas and warming can also increase root N uptake capacity (Cao et al, 2020; Jiang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…accelerate climatic warming, catalyzing a positive feedback loop (Woodwell & Mackenzie, 1995) and reducing the C available for plant biomass production (Jarvi & Burton, 2018). However, if root respiration acclimatizes to increasing temperature, the potential negative effects of warming on net C increases in plants and ecosystems will be greatly reduced (Jarvi & Burton, 2018).…”
mentioning
confidence: 99%